Structural, thermal and dielectric properties of rare earth substituted eulytite for LTCC applications. Issue 8 (July 2016) - Abhilash, Pullanchiyodan; Sebastian, Mailadil Thomas; Surendran, Kuzhichalil Peethambharan
Abstract: A new series of LTCC compositions having the general formula Bi3.9 RE0.1 (SiO4 )3 where, (RE = Yb, Tm, Er, Gd, Sm, Nd, Pr) were developed. The crystal structure analysis using Rietveld refinement of the powder diffraction data of all compositions confirmed partial substitution of rare earth at bismuth site. The microwave dielectric and thermal properties of these new LTCC compositions were studied. Some of the rare earth substituted compound namely, Bi3.9 Tm0.1 (SiO4 )3, Bi3.9 Sm0.1 (SiO4 )3, show improvement in Q u × f value (22, 600 GHz and 24, 100 GHz respectively at 8.2 GHz) as compared to the parent Bi4 (SiO4 )3 (20, 500 GHz, at 8.2 GHz).